Effects of captions and English proficiency on learning effectiveness, motivation and attitude in augmented-reality-enhanced theme-based contextualized EFL learning. Issue 3 (4th March 2022) - Chen, Ming-Puu; Wang, Li-Chun; Zou, Di; Lin, Shu-Yuan; Xie, Haoran; Tsai, Chin-Chung
Abstract: Augmented reality (AR) deepens learning interactions by imposing digital information on top of physical settings. This study implemented an AR-enhanced theme-based contextualized learning and aimed to examine the effects of captions (non-caption, English caption and Chinese caption) and English proficiency (less proficient and proficient) on junior high school students' English learning effectiveness, motivation and attitude. Six classes of ninth-graders voluntarily participated in the experimental learning sessions using tablets. A factorial design was employed, and the participants' learning performance, motivation and attitude were evaluated. The results indicated that captions did not affect knowledge comprehension, but English proficiency played a significant role in it. The effects of captions and English proficiency on knowledge application indicated that English captions placed high cognitive load and hindered less proficient learners' knowledge application, but proficient learners performed equally under different caption conditions. Generally, students demonstrated positive motivation toward learning from the AR-enhanced contextualized learning. The proficient learners were more motivated in terms of self-efficacy, proactive learning and learning value. All learners expressed positive attitude toward learning, among whom, those who learned without captions showed greater degrees of confidence and preferences, and the proficient learners showed greater degrees of confidence, preferences, learning process and learning strategy but lower degrees of anxiety.